Environmental regulation in the new global economy the impact on industry and competitiveness - Jenkins, Rhys Owen, 1948-; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : E. Elgar, 2002)
This book attempts to answer these questions using case studies of three pollution-intensive industries: iron and steel, leather tanning, and fertilizers. Based on in-depth interviews with managers and regulators in Western and Eastern Europe, Asia, Africa and Latin America, the book illustrates the variety of responses to the conflicting pressures of globalization and environmental protection at corporate and industry levels.
pt. 1. An overview / by Rhys Jenkins -- pt. 2. Environmental regulations, globalization of production and technological change : the iron and steel sector / by Jonathan Barton -- pt. 3. Leather tanning : environmental regulations, competitiveness and locational shifts / by Jan Hesselberg and Hege Merete Knutsen -- pt. 4. Environmental regulation and industrial restructuring : the case of the fertilizer industry / by Anthony Bartzokas -- pt. 5. Conclusion / by Rhys Jenkins.
Papers resulted from a conference held in 1999 at the University of East Anglia.
Includes bibliographical references (p. 315-335) and index.
Keywords: Environmental policy -- Economic aspects -- Europe -- Congresses; Environmental policy -- Economic aspects -- Developing countries -- Congresses; Environmental law -- Compliance costs -- Europe -- Congresses; Environmental law -- Compliance costs -- Developing countries -- Congresses; Factory and trade waste -- Environmental aspects -- Europe -- Congresses; Factory and trade waste -- Environmental aspects -- Developing countries -- Congresses; Globalization -- Environmental aspects -- Europe -- Congresses; Globalization -- Environmental aspects -- Developing countries -- Congresses; Competition, International -- Congresses; Electronic books